The effect of habitat structure on prey mortality depends on predator and prey microhabitat use - Klecka, Jan; Boukal, David S (Oecologia, 2014)
Structurally complex habitats provide cover and may hinder the movement of animals. In predator-prey relationships, habitat structure can decrease predation risk when it provides refuges for prey or hinders foraging activity of predators. However, it may also provide shelter, supporting structures and perches for sit-and-wait predators and hence increase their predation rates. We tested the effect of habitat structure on prey mortality in aquatic invertebrates in short-term laboratory predation trials that differed in the presence or absence of artificial vegetation. The effect of habitat structure on prey mortality was context dependent as it changed with predator and prey microhabitat use. Specifically, we observed an 'anti-refuge' effect of added vegetation: phytophilous predators that perched on the plants imposed higher predation pressure on planktonic prey, while mortality of benthic prey decreased. Predation by benthic and planktonic predators on either type of prey remained unaffected by the presence of vegetation. Our results show that the effects of habitat structure on predator-prey interactions are more complex than simply providing prey refuges or cover for predators. Such context-specific effects of habitat complexity may alter the coupling of different parts of the ecosystem, such as pelagic and benthic habitats, and ultimately affect food web stability through cascading effects on individual life histories and trophic link strengths.
Keywords: Seasons; mortalita; Insecta; ekosystém; Česká republika; lineární modely; hmyz; Predatory Behavior; Czech Republic; potravní řetězec; Linear Models; predátorské chování; zvířata; Mortality; Zooplankton; zooplankton; Food Chain; Ecosystem; roční období; Animals